Changes in alcohol use, PTSD hyperarousal symptoms, and intervention dropout following veterans' use of VetChange. (August 2020) - Livingston, Nicholas A.; Mahoney, Colin T.; Ameral, Victoria; Brief, Deborah; Rubin, Amy; Enggasser, Justin; Litwack, Scott; Helmuth, Eric; Roy, Monica; Solhan, Marika; Rosenbloom, David; Keane, Terence
Highlights: We examined VetChange outcomes and dropout to guide future intervention development. VetChange users reported significant alcohol reductions in the first 30 days. Alcohol reduction predicted higher hyperarousal but not overall PTSD severity. Hyperarousal symptoms and hypervigilance specifically predicted VetChange dropout. Web interventions that are responsive to time-varying symptom change are needed. Abstract: Objective: Veterans of Iraq and Afghanistan conflicts report high rates of drinking, PTSD, and low rates of treatment engagement. Web interventions may help address unmet treatment need; unfortunately, little is known regarding outcomes or adherence to these interventions. In this study, we examined VetChange treatment outcomes and downstream effects of alcohol reduction on PTSD symptoms and intervention dropout rates over six months. Method: Participants included 222 veterans (77.5% men, 78.3% White) between 22 and 57 (mean age = 36.02, SD  = 7.19). All VetChange users completed a brief alcohol assessment and received personal feedback, then received full access to intervention content including psychoeducation; motivational and cognitive-behavioral modules for relapse prevention, goal-setting, social support, stress, anger, and sleep management; and mood and drink tracking. Veterans completed self-report measures of alcohol use and PTSD symptoms at baseline, one, three, and six months. Results: Alcohol use dropped by 43% over six months, p  < .001, with the largest decrease occurring within the first month. Greater alcohol reduction in the first month predicted higher subsequent PTSD hyperarousal severity. Over half (52.3%) dropped out by month one, followed by 12.2% and 37.6% by months three and six. Hyperarousal symptoms, hypervigilance specifically, but not alcohol use predicted subsequent intervention dropout. Conclusion: These results highlight the importance of attending to the association between alcohol use and PTSD symptom change in web-based interventions for veterans. The fact that hyperarousal symptoms were associated with elevated risk for intervention dropout signifies the need for online intervention refinement aimed at tailoring content to time-varying symptom presentations.